Pro-efferocytic nanotherapies reduce vascular inflammation without inducing anemia in a large animal model of atherosclerosis - Sharika Bamezai; Yapei Zhang; Manisha Kumari; Mozhgan Lotfi; Tom Alsaigh; Lingfeng Luo; Gayatri Suresh Kumar; Fudi Wang; Jianqin Ye; Madhu Puri; Romila Manchanda; Sesha Paluri; et al. (Nature Communications, 2024)
Abstract Atherosclerosis is an inflammatory disorder responsible for cardiovascular disease. Reactivation of efferocytosis, the phagocytic removal of cells by macrophages, has emerged as a translational target for atherosclerosis. Systemic blockade of the key ‘don’t-eat-me’ molecule, CD47, triggers the engulfment of apoptotic vascular tissue and potently reduces plaque burden. However, it also induces red blood cell clearance, leading to anemia. To overcome this, we previously developed a macrophage-specific nanotherapy loaded with a chemical inhibitor that promotes efferocytosis. Because it was found to be safe and effective in murine studies, we aimed to advance our nanoparticle into a porcine model of atherosclerosis. Here, we demonstrate that production can be scaled without impairing nanoparticle function. At an early stage of disease, we find our nanotherapy reduces apoptotic cell accumulation and inflammation in the atherosclerotic lesion. Notably, this therapy does not induce anemia, highlighting the translational potential of targeted macrophage checkpoint inhibitors.